PEDAGOGICAL CHALLENGES AND INNOVATIONS IN THE TRAINING OF HORECA SPECIALISTS: UKRAINIAN AND GLOBAL CONTEXTS - Budnyk, Nina; Moroz, Svitlana; Kalashnyk, Olena; Levchenko, Yulia (SWorld-Ger Conference proceedings, 2025)
The study examines the system of professional training for specialists in the HoReCa sector within the context of Ukrainian and international educational practices. It analyzes the main challenges facing domestic vocational education under crisis conditio